New iron-based fluoride cathode material synthesized by non-aqueous ionic liquid for rechargeable sodium ion batteries. (20th December 2015) - Jiang, Miaoling; Wang, Xianyou; Shen, Yongqiang; Hu, Hai; Fu, Yanqing; Yang, Xiukang
Highlights: The like-cubic pyrochlore Fe2 F5  · H2 O is prepared by non-aqueous IL based precipitation. The Fe2 F5  · H2 O is firstly reported as the cathode material for sodium ion batteries. Fe2 F5  · H2 O shows the sphere-like morphology and good dispersity. Electrochemical properties are greatly improved by forming graphene-loaded Fe2 F5  · H2 O. Abstract: A pyrochlore Fe2 F5  · H2 O composite with a much larger cell volume and the interconnected open 3D channel is firstly synthesized by ionic liquid (IL) based precipitation route and used as the cathode material of sodium ion batteries (SIBs). The morphology, structure and physicochemical properties as well as electrochemical performance are characterized by X-ray powder diffraction (XRD), Rietveld refinement of XRD pattern, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and electrochemical tests. It has been found that Fe2 F5  · H2 O is a face-centered cubic crystal structure with high crystallinity, and iron in the Fe2 F5  · H2 O is in the form of mixed valence states. Moreover, the Fe2 F5  · H2 O sample shows the sphere-like morphology with the average particle about 700 nm and good dispersity. Besides, the Fe2 F5  · H2 O shows a high initial discharge capacity of 253.7 mAh g −1 and the reversible capacity of 161.2 mAh g −1 at 20 mA g −1 in the voltage of 1.0–4.0 V. After modification by graphene, the Fe2 F5  · H2 O/graphene (abbreviated as Fe2 F5  · H2 O/G) composite reveals good cycling stability and high rate performance. Consequently, the Fe2 F5  · H2 O may be a potential cathode material for SIBs system.